Genetic analysis of the human prohibitin gene (PHB) in breast and other cancers - Hagan, Richard (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2000)
Prohibitin, an evolutionarily conserved gene situated on chromosome 17q21, was originally identified as a gene with antiproliferative properties. Studies of a Japanese population have shown prohibitin to be somatically mutated in a proportion of breast tumours. The gene has not heretofore been shown to have an association with inherited forms of breast or other cancers. In this thesis the technique of denaturing gradient gel electrophoresis (DGGE) was developed to analyse the complete coding sequence of the prohibitin gene from fragments generated by the polymerase chain reaction (PCR). This was achieved by examining the melting profiles of different regions of the prohibitin sequence with the melt map program MELT87. Four overlapping fragments were designed and subsequently amplified by reverse transcription PCR thus enabling analysis of the prohibitin cDNA sequence by DGGE. A further five fragments were developed for analysis of prohibitin from genomic DNA. These five fragments were generated for exons 3-7 inclusive. By investigating the prohibitin gene in this way a total of 5 novel mutations were identified; one missense mutation in exon 3 (Arg43Leu), one silent mutation in exon 5 (Leu145Leu) and three intronic base substitutions, two in intron 6 and one in intron 3. Nucleotide alterations were determined by sequencing of PCR products.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin